2009
DOI: 10.1111/j.1439-0272.1994.tb00750.x
|View full text |Cite
|
Sign up to set email alerts
|

Glass wool filter preparation of cryopreserved spermatozoa

Abstract: Oligozoospermic and asthenozoospermic semen ejaculates, as well as cryopreserved sperm samples prepared by the wash and swimup procedure often result in unsatisfactory sperm recovery rates. In this study the glass wool filter and the wash and swim-up preparation procedures were compared on the basis of their 'effective' (number of live sperm per millilitre) recovery rates. The glass wool filter procedure consistantly produced significantly (P= 0.0002) higher viable sperm concentrations, making it the preferred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…Finally, the sperm were capable of fertilizing buffalo oocytes in vitro, displaying cleavage rates similar to those processed through swim-up method. Our results are in line with those of previous studies where improvement in sperm quality using GWF was reported in dog, human and bovine (Anzar & Graham, 1996;Anzar et al, 1997;Coetzee, Erasmus, Kruger, Menkveld, & Lombard, 1994;Gunay, Zekariya, & Kemal, 2004;Vyas et al, 1992), while fertilization rates were found comparable in bovine sperm prepared by glass wool filtration and swim-up (Stubbings & Wosik, 1991). (Samper et al, 1995).…”
Section: Discussionsupporting
confidence: 93%
“…Finally, the sperm were capable of fertilizing buffalo oocytes in vitro, displaying cleavage rates similar to those processed through swim-up method. Our results are in line with those of previous studies where improvement in sperm quality using GWF was reported in dog, human and bovine (Anzar & Graham, 1996;Anzar et al, 1997;Coetzee, Erasmus, Kruger, Menkveld, & Lombard, 1994;Gunay, Zekariya, & Kemal, 2004;Vyas et al, 1992), while fertilization rates were found comparable in bovine sperm prepared by glass wool filtration and swim-up (Stubbings & Wosik, 1991). (Samper et al, 1995).…”
Section: Discussionsupporting
confidence: 93%
“…Filtration through a Sephadex column [1,2,21] and isolation by density gradient centrifugation in Percoll [27,35] have allowed improvements in the quality of bovine semen. In cases of high viscosity [34,46], poor semen quality [23] or cryopreserved ejaculates [8], the glass wool filtration method has proved to be advantageous [12]. …”
Section: Introductionmentioning
confidence: 99%
“…However, comparative data concerning the effectiveness of biophysical treatment methods such as Sephadex, glass wool and Percoll in cryopreserved bovine semen has been lacking, although previous experiments have established that various semen manipulation techniques increase the qualitative features of spermatozoa [8,23,27,35]. Also, very few reports are available regarding IVF results of spermatozoa isolated by Sephadex and glass wool filtration despite their excellent ability to improve sperm quality in post-thaw bovine and other species semen [46].…”
Section: Introductionmentioning
confidence: 99%
“…In humans, spermatozoa separated with GWF yield a sample enriched for motility, morphologically normal spermatozoa, and good chromatin condensation, as well as having a high recovery rate and good cleavage and blastocyst rates [ 97 , 98 ]. GWF was also shown to produce a sufficient number of cells, with better recovery than SU, for insemination with frozen-thawed spermatozoa [ 99 ]. In an experiment with bovine sperm comparing DGC and GWF, GWF was capable of enriching motility, membrane integrity, and GWF-selected sperm used for IVF resulted in higher cleavage and blastocyst rates than control samples [ 100 ].…”
Section: Sorting Semen: Significance and Methodsmentioning
confidence: 99%